Snack Safety Identification through Information on Snack Packaging to Elementary Students - Yusni Atifah; Afifatul Achyar (Pelita Eksakta, 2022)
Snack types of chips, biscuits are sold using packaging. The snack packaging contains important information related to the nutritional component of the snack, expiration date, product halalness and other important information that is important for buyers to know. Elementary school students have insufficient attention and knowledge related to the information on snack packaging so that it can result in adverse conditions for elementary school students if they consume snacks that are not good for health. As a preventive step, it is necessary to educate elementary school children, one of which is knowledge of how to identify the meaning of symbols and information found on snack packages. The methods used in this activity are lectures and discussions by conveying information to elementary school students about the information found on snack packages and demonstrating several pictures and ways to identify symbols found on snack packages. The results of the evaluation showed that the students enthusiastically participated in this activity. In addition, there is also an increase in students' knowledge and ability to explain the symbols and information found on snack packaging.